On the Immorality and Futility of Canadian Climate Policy under Trudeau. Issue 4 (2nd October 2021) - MacNeil, Robert
ABSTRACT: This paper argues that Canadian climate policy under the Trudeau government is both self-defeating and immoral. Focusing on the central facet of the government's strategy – which trades a small carbon price for significant expansions of oil pipelines – the paper develops this argument in three principal ways. First, it situates the strategy in relation to the global warming potential of new extracted/exported emissions facilitated by new pipelines, which would overwhelm the savings created by the carbon price. Second, the paper focuses on the policy's potential to exacerbate a perilous national accumulation strategy that leaves workers and communities highly vulnerable to unstable global commodity markets. Finally, it situates the policy in relation to a centuries-old process of colonial theft of Indigenous lands to facilitate extractive development. The paper closes by considering what an environmentally sound and morally just Canadian climate policy would look like along eco-socialist lines.